The Resistance of Chagasic Wistar Rat Offspring to Reinfections by Trypanosoma cruzi - Nora Mogollón; Elio Moreno; Maritza Alarcón; Ana Lugo de Yarbuh; Martha Ramírez; Rafael Borges (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
The resistance to reinfection by Trypanosome cruzi in chagasic rat offspring was evaluated. Thirty male offspring () from infected mothers and 30 offspring from healthy mothers were used, divided into groups of 10 offspring each (I, II, III) and (IV, V, VI). The groups (I, IV) and (II, V) were inoculated and reinoculated by intradermal route with 5 × 104 metacyclic trypomastigotes of homologous (pL) and heterologous (Y) strains of T. cruzi, from laboratory infected Rhodnius prolixus, at one-month intervals. The control groups (III, VI) received saline injections. The parasitological and serological testing performed on both groups of infected offspring at 10, 20 and 30 days post-reinoculation (pr) showed significantly higher parasitemia levels in offspring from healthy mothers during the acute phase of the primary infection, the absence of bloodstream trypomastigotes after the 1st and 2nd reinoculation, and a significant increase in anti-T. cruzi antibody levels after initial inoculation and reinoculations. The histopathological and immunohistochemical analysis of heart and skeletal muscle sections from the offspring sacrificed at 45, 75 and 105 days pi, revealed the gradual establishment of myocarditis and acute myositis of variable intensity accompanied by few nests of amastigotes, a worsening of the pathologic picture produced by the initial inoculation, and the presence of abundant antigenic deposits that intensified with the reinoculations. In conclusion, the resistance of offspring born from chm to homologous and heterologous reinfection by T. cruzi strains, is produced, first, by vertical transmission of the parasites and/or humoral antibodies from infected mothers to their progeny, and second, by a sensibilization process in the host from continuous antigenic downloads produced when the inoculated parasites are destroyed.